Perkembangan Olahraga Goboy di Kota Kediri Jawa Timur - Sukmana, Abdian Asgi; Weda; Rafi, Sultan Achmad (MAN Insan Cendekia Jambi, 2024)
The purpose of this research is to demonstrate the development of the Goboy sport in the region of Kediri City, East Java Province. The research method is descriptive qualitative using observation, interview, and documentation techniques to study the phenomenon of Goboy sports development in the city of Kediri. In this case, the research subjects are school institutions, students, and supervising teachers, as well as the phenomena of activities such as playing, socializing, and Goboy competitions. The subjects of this research are the Elementary School level, Junior High School level (SMP), and Senior High School level (SMA) or Vocational School (SMK) in the city of Kediri, both public and private. The data collection results revealed three activities: 1) training activities or PJOK learning activities during free time, 2) socialization activities, and 3) competitions among students throughout the City of Kediri. The conclusion of this research states that public and private elementary and junior high schools that have received socialization are considered to have understood the Goboy sports game, with a result of 100% from a total of 138 elementary schools and 34 junior high schools. As for SMA/SMK, three activities have been carried out, with 2 schools directly socializing with their students, namely SMAN 3 and SMAN 7, and 12 schools participating in the Goboy competition out of a total of 27 schools, resulting in an outcome of 44.8% who are considered to know and practice the Goboy sport.